The Effect of The Work Environment and Compensation on Employee Performance at PT. Mataram Duta Abadi - Tan Marcella Wijaya; Wulandari , Wulandari (Jurnal Ekonomi, 2024)
From year to year the textile industry has a strategic impact on industrialization and provides a surplus to the trade balance. Developments can be seen from increasing market demand and export activity. The aim of the research is to analyze the influence of the Work Environment and Compensation on Employee Performance. The research method uses quantitative methods to examine certain samples or populations using random sampling techniques. The research population was 54 respondents. The research results show that the work environment and compensation have a positive and simultaneous effect on employee performance.